Evaluation of early life experiences: the eles scale and its clinical use - León-Palacios, María G.; Garrido-Fernández, Miguel; Senín-Calderón, Cristina; Perona-Garcelán, Salvador; Gilbert, Paul; Rodríguez-Testal, Juan F. (Anales de Psicología / Annals of Psychology, 2019)
Background: The Early Life Experiences Scale (ELES) evaluates the memory of threat and subordination perceived in childhood family relationships based on social rank theory. This scale was adapted to Spanish, its factor structure was tested by cross-validation, and its psychometric properties were explored. Method: 960 subjects participated (863 subjects from the general population and 97 patients). Results: Data confirm the factor structure of the original version by Authors (2003), obtaining a similar model with three factors: submission, threat, and devaluation, which explained 66.31% of the variance. The Spanish version of the ELES was comprised of the same number of items as in the original study and showed adequate indices of validity, internal consistency, retest and combined reliability. Conclusions: The Early Life Experiences Scale (ELES) can be a useful measure for evaluating early life experiences. Its application may be very relevant in studying the relationship between these experiences and psychopathological manifestations in constructing explanatory models.